2019
DOI: 10.1097/txd.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Monoclonal Gammopathy of Undetermined Significance in Kidney Transplant Recipients

Abstract: Background.It is unclear if immunosuppression increases the likelihood of malignant transformation of monoclonal gammopathy of undetermined significance (MGUS) and whether adverse renal outcomes in kidney transplant recipients with MGUS are more frequent.Methods.We performed a retrospective cohort study of kidney transplant recipients at the Centre Hospitalier de l’Université de Montréal between 2000 and 2016.Results.Among 755 study participants, 13 (1.7%) were found to have MGUS before transplant. Two evolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…In a large retrospective study, Goebel et al found that individuals with MGUS pre‐transplant did not have an increased risk of developing PCM post‐solid organ transplantation, and Jimenez‐Zepeda et al have argued against routine testing for MGUS before transplantation as it lacks prognostic value 59,60 . No increase in the risk of progression of PT‐MGUS to PCM has also been documented by several investigators 56,57 . Moreover, spontaneous resolution of MGUS has been reported in 21%‐37% of solid organ allograft recipients, compared to 2% of non‐transplant patients 56,57,61 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a large retrospective study, Goebel et al found that individuals with MGUS pre‐transplant did not have an increased risk of developing PCM post‐solid organ transplantation, and Jimenez‐Zepeda et al have argued against routine testing for MGUS before transplantation as it lacks prognostic value 59,60 . No increase in the risk of progression of PT‐MGUS to PCM has also been documented by several investigators 56,57 . Moreover, spontaneous resolution of MGUS has been reported in 21%‐37% of solid organ allograft recipients, compared to 2% of non‐transplant patients 56,57,61 .…”
Section: Discussionmentioning
confidence: 97%
“…55 in the general population, with a 30% 25-year cumulative probability of progression to MM. 12 The 5-year cumulative incidence of MGUS in solid organ allograft recipients has ranged from 4% to 10.7% and a prevalence of 8.1% has been reported, [56][57][58] which is higher than the general population. Serum paraprotein analysis prior to organ transplantation was only performed for one patient in our series and the possibility of before transplantation as it lacks prognostic value.…”
Section: Morphology and Immunophenotypementioning
confidence: 99%
See 2 more Smart Citations
“…In their series of 755 kidney transplant patients over 16-y period, a group from Montreal performed pretransplant serum protein electrophoresis (SPEP) in 375 patients, whereas 380 patients had SPEP only after kidney transplantation. 12 Thirteen out of 375 patients were identified with MGUS before transplant with 4 of these patients progressing to either smoldering multiple myeloma or light chain deposition disease posttransplantation. Forty-three patients in their cohort were diagnosed with MGUS posttransplantation with only 2 patients progressing to either multiple myeloma or light chain deposition disease.…”
Section: Progression Of Mgus To Clinically Significant Plasma Cell Disorders After Kidney Transplantationmentioning
confidence: 99%